Student Learning Style in High School History Learning Process Towards Achievement Improvement - Susilo, Agus; Sustianingsih, Ira Miyarni (Edukasi, 2021)
The background of this research is that the current history learning system determines the achievement of students at the high school level. This is based on the different learning styles of each student's character. The purpose of this study was to determine students' learning styles in the history of high school learning process towards increasing achievement. The learning style of students determines the enthusiasm in learning High School History. This research method is descriptive analysis with qualitative studies. Sources in this study are the results of interviews and review sources of journal references that are relevant to the research study. The results of the study were: History learning in the era of globalization is currently experiencing a change in history learning in school teaching. In addition to the increasingly developing curriculum, the emphasis of History learning is more emphasized on the value of good ethical attitudes. While the learning styles of high school students towards learning History are in accordance with the progress of times and technology, History teachers must be able to innovate so that History learning becomes interesting. Each student has a different way of studying History learning. The role of the History teacher in packaging History lessons to be interesting is very important. The conclusion of this research is that history learning must be adjusted to the increasingly sophisticated progress of the times. The increase in student achievement in studying History must be enhanced by the use of media reference sources and other historical sources. The new finding that the researcher found was that teachers and students had to work together in studying history. History teachers must be open to technology that provides benefits for learning History. The benefits for history will be sustainable if they are packaged properly. In addition, studying History will make humans wiser in the present and in the future.